Negotiation diplomacy in American foreign policy - Kadhim, Dr. Ali Jawad; Mataroud, Ass.Lecture Ibtisam Mahdi (Thi Qar Arts Journal, 2023)
No country in the world has enjoyed the capabilities of a huge power and technological and technical capabilities that enable it to use them according to the situation and nature of the discharge of affairs in it, which made it the decisive power in international conflicts, and it depends on its attractiveness largely on the values ​​that it expresses in its foreign policy and its style in negotiation, and soft power depends as an element of attraction in mobilizing and cooperating with others without resorting to the use of coercion, and that measuring the effectiveness of diplomacy depends on the ability to employ soft power in achieving the objectives of American foreign policy.